2022
DOI: 10.56899/151.01.33
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Low-cost Storage Structures for Onions (Allium cepa L.) Storage in Bahir Dar, Amhara Region, Ethiopia

Abstract: The effect of fully ventilated storage structure, netted bags, mud-coated structure (local practice in the region), and heap storage on quality and shelf-life of onion cv. Bombay red was studied at Bahir Dar Institute of Technology in Ethiopia. The experiment was conducted in a single factor with four levels (four storage structures) with three replications. Manually harvested and cured onions were stored in different storage structures and different quality and shelf-life properties were studied for 90 d. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Te titratable acidity of onion was 1.77%. Te previous study reported titratable acidity in the range 1.2-2.3% for onion bulbs for diferent storage condition and time [9], which is in agreement with the current study.…”
Section: Ph and Titratable Aciditysupporting
confidence: 93%
See 2 more Smart Citations
“…Te titratable acidity of onion was 1.77%. Te previous study reported titratable acidity in the range 1.2-2.3% for onion bulbs for diferent storage condition and time [9], which is in agreement with the current study.…”
Section: Ph and Titratable Aciditysupporting
confidence: 93%
“…Te previous study that was conducted on green paper grown under open feld and green house condition reported a TSS value in the range of 3.2 to 10.0 °Brix [34], which agrees well with the current study. A study that was conducted on onion under diferent storage structures and storage time reported a TSS in the range of 10.53 to 13.29 °Brix [9], which is in agreement with this study. [36]; this may be due to the diference in the variety of the red pepper, the maturity, or growing environment.…”
Section: Total Soluble Solid (Tss)supporting
confidence: 91%
See 1 more Smart Citation
“…The results fluctuate with the environmental conditions (Eriballo et al, 2021). Physiological weight loss is greater than before as the storage period proceeded (Kumar & Dhankhar, 2023).…”
Section: Original Research Articlementioning
confidence: 86%
“…Eriballo et al. (2022) found that fully ventilated storage structures in Ethiopia minimized sprouting, mold incidence, and rotting in onions over a 90‐day storage period. Quality parameters such as TSS, firmness, ascorbic acid, and marketable onions improved.…”
Section: Storage Systems For Onionsmentioning
confidence: 99%